Work‐from‐anywhere: The productivity effects of geographic flexibility. (22nd November 2020) - Choudhury, Prithwiraj (Raj); Foroughi, Cirrus; Larson, Barbara
Abstract: Research Summary: An emerging form of remote work allows employees to work‐from‐anywhere, so that the worker can choose to live in a preferred geographic location. While traditional work‐from‐home (WFH) programs offer the worker temporal flexibility, work‐from‐anywhere (WFA) programs offer both temporal and geographic flexibility. WFA should be viewed as a nonpecuniary benefit likely to be preferred by workers who would derive greater utility by moving from their current geographic location to their preferred location. We study the effects of WFA on productivity at the United States Patent and Trademark Office (USPTO) and exploit a natural experiment in which the implementation of WFA was driven by negotiations between managers and the patent examiners' union, leading to exogeneity in the timing of individual examiners' transition from a work‐from‐home to a work‐from‐anywhere program. This transition resulted in a 4.4% increase in output without affecting the incidence of rework. We also report results related to a plausible mechanism: an increase in observable effort as the worker transitions from a WFH to a WFA program. We employ illustrative field interviews, micro‐data on locations, and machine learning analysis to shed further light on geographic flexibility, and summarize worker, firm, and economy‐wide implications of provisioning WFA. Managerial Summary: Work‐from‐anywhere is an emerging form of remote work, in which workers are awarded geographic flexibility, that is, the flexibility to choose where to live. We study the productivity effects of workers moving from a work‐from‐home (WFH) to a work‐from‐anywhere (WFA) regime at the United States Patent and Trademark Office (USPTO). Exploiting a natural experiment, we find that the transition from WFH to WFA resulted in a 4.4% increase in employee output, with no increase in rework. We also report an increase in employee effort after the transition to WFA and document qualitative evidence on how geographic flexibility benefits individual workers and the USPTO (e.g., real estate savings).